The role of N-β-alanyldopamine synthase in the innate immune response of two insects - Schachter, Julieta (2007)
Insects trigger a multifaceted innate immune response to fight microbial infections. We show that in the yellow mealworm, Tenebrio molitor, septic injuries induce the synthesis of N-b-alanyldopamine (NBAD), which is known as the main sclerotization precursor of insect brown cuticles. We demonstrate that NBAD synthase is induced in the epidermis of the mealworm and of the Medfly, Ceratitis capitata, by infection with Escherichia coli. Our results indicate that synthesis of NBAD seems to be a novel component of the overall innate immune response in insects.